2020
DOI: 10.3390/electronics9040640
|View full text |Cite
|
Sign up to set email alerts
|

Towards Traffic Identification and Modeling for 5G Application Use-Cases

Abstract: To analyze next-generation mobile networks properly, there is a need to define key performance indicators (KPIs). Testing signaling only or just partial domains of the network have been replaced with end-to-end testing methodologies. With the appearing of machine-to-machine (M2M) applications, this question became even harder, since there is no direct user feedback. Quality of experience cannot be measured accurately in M2M applications, even if the network operates correctly and without failures. There are do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Based on our previous works in [ 44 ], we identified measurement scenarios with different PL and IAT parameters. Besides, one reference scenario was measured with constant parameters.…”
Section: 5g Technology Based Measurement Resultsmentioning
confidence: 99%
“…Based on our previous works in [ 44 ], we identified measurement scenarios with different PL and IAT parameters. Besides, one reference scenario was measured with constant parameters.…”
Section: 5g Technology Based Measurement Resultsmentioning
confidence: 99%
“…As descibed, this is a Non-Standalone 5G architecture, which uses the LTE EPC, and LTE eNB for uplink radio communications. In order to present a reference comparison, we have carried out similar measurements on earlier 4G [ 23 ]—and those results also apply here, since we used the exact same 5G environment. The aggregated results ( Table 3 ) show that, for peak rates, the 5G scenario performs much better than 4G.…”
Section: Measurement Resultsmentioning
confidence: 99%
“…For comparisons, one reference scenario was also measured with constant parameters. The examined state-space scenarios are as follows: Based on preliminary measurements [23], we found that the maximum MTU size on the network is 1450 Byte without segmentation. Still, as measurement scenario 2 and 3 suggests, we also used packets with PLs that were greater than 1450 Byte to characterize this kind of network behavior.…”
Section: Measurement Methodologymentioning
confidence: 99%
See 2 more Smart Citations